Identification of Bacteria Sample Plaque from Periodontal Disease Among Diabetic Patients - Shahida Mohd-Said; Nur Fatimah Zaharah Salehuddin; Siti Nursyuhada Jafar; Tuti Ningseh Mohd-Dom; Haslinda Ramli; Rohazila Mohamad Hanafiah (JK Welfare & Pharmascope Foundation, 2024)
Volume 21 Issue 1 Page (366-373)